2021
DOI: 10.1002/ece3.7380
|View full text |Cite
|
Sign up to set email alerts
|

Dhole pack size variation: Assessing the effect of Prey availability and Apex predator

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 68 publications
(78 reference statements)
0
21
0
Order By: Relevance
“…Therefore, cooccurring carnivore species are expected to have evolved morphological and behavioral adaptations to reduce risks of intraguild competition (Schoener, 1982;Hunter and Caro, 2008). Competitive interactions among the carnivores can result in top carnivores limiting the populations of subordinate carnivores (Creel and Creel, 1996;Donadio and Buskirk, 2006;Bhandari et al, 2021), feeding interference (Linnell and Strand, 2000), or even intraguild predation (Creel and Creel, 1996;Holt and Polis, 1997). Specializing on different food resources is an effective strategy to reduce the predation competition in coexisting carnivores over a long evolutionary time (Connell, 1980;Jones and Barmuta, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, cooccurring carnivore species are expected to have evolved morphological and behavioral adaptations to reduce risks of intraguild competition (Schoener, 1982;Hunter and Caro, 2008). Competitive interactions among the carnivores can result in top carnivores limiting the populations of subordinate carnivores (Creel and Creel, 1996;Donadio and Buskirk, 2006;Bhandari et al, 2021), feeding interference (Linnell and Strand, 2000), or even intraguild predation (Creel and Creel, 1996;Holt and Polis, 1997). Specializing on different food resources is an effective strategy to reduce the predation competition in coexisting carnivores over a long evolutionary time (Connell, 1980;Jones and Barmuta, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Both the protected areas are separated by an average distance of 200 kms and interspersed by human habitation and roads possibly acting as a barrier for gene flow. Apart from physical differences, both tiger reserves exhibit an interesting sympatric predator dynamic due to comparative differences in tiger population and pack size variation (Bhandari et al, 2021).…”
Section: Study Areamentioning
confidence: 99%
“…A study done on red colobus monkeys found that female dispersal is more frequent in larger groups to avoid the increased competition for food resources within the group (Miyamoto et al, 2013). In the case of dholes, there is also a significant difference in the average pack size: a larger pack in Nawegaon-Nagzira Tiger Reserve (NNTR) and a smaller pack size in Tadoba-Andhari Tiger Reserve (TATR) within the landscape (Bhandari et al, 2021). The wide-scale assessment of local patterns of variation in pack size showed a significant inverse relationship between tiger density and pack size of dhole while accounting for the variability in resources and habitat heterogeneity (Bhandari et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations